Geopolitical imaginations of Russia in the region of the central and eastern Europe - Novak, N. (2020)
The aim of the paper is to explore whether contemporary Russian Federation has imaginations of its power in the region of the Central and Eastern Europe. Using a theoretical framework based on instruments, notions and tools of critical geopolitics, this paper discusses four discourses that define the territory which is the focus of the research, as well as stressing the most important concepts of contemporary foreign policy of the Russian Federation. Due to the strong influence of NATO’s (and the EU’s) enlargement policies in this region, the Russian administration tries to preserve its traditional geopolitical sphere of interest in the European continent. Therefore, three sub-regional case studies— annexation of Crimea in the Eastern Europe, the Three Seas Initiative in the Central Europe, and Western Balkan’s case study of Montenegro’s path to full NATO membership—will be explored to examine this hypothesis. Finally, adequate conclusion, regarding the main hypothesis, is brought.